Development of a Genome-Edited Tomato With High Ascorbate Content During Later Stage of Fruit Ripening Through Mutation of SlAPX4 - Do, Ju Hui; Park, Seo Young; Park, Se Hee; Kim, Hyun Min; Ma, Sang Hoon; Mai, Thanh Dat; Shim, Jae Sung; Joung, Young Hee (Frontiers in Plant Science, 2022)
Ascorbate is an essential antioxidant substance for humans. Due to the lack of ascorbate biosynthetic enzyme, a human must intake ascorbate from the food source. Tomato is one of the most widely consumed fruits, thus elevation of ascorbate content in tomato fruits will improve their nutritional value. Here we characterized Solanum lycopersicum ASCORBATE PEROXIDASE 4 (SlAPX4) as a gene specifically induced during fruit ripening. In tomatoes, ascorbate accumulates in the yellow stage of fruits, then decreases during later stages of fruit ripening. To investigate whether SlAPX is involved in the decrease of ascorbate, the expression of SlAPXs was analyzed during fruit maturation. Among nine SlAPXs, SlAPX4 is the only gene whose expression was induced during fruit ripening. Mutation of SlAPX4 by the CRISPR/Cas9 system increased ascorbate content in ripened tomato fruits, while ascorbate content in leaves was not significantly changed by mutation of SlAPX4. Phenotype analysis revealed that mutation of SlAPX4 did not induce an adverse effect on the growth of tomato plants. Collectively, we suggest that SlAPX4 mediates a decrease of ascorbate content during the later stage of fruit ripening, and mutation of SlAPX4 can be used for the development of genome-edited tomatoes with elevated ascorbate content in fruits.